A novel chitin‐binding mode of the chitin‐binding domain of chitinase A1 from Bacillus circulans WL‐12 revealed by solid‐state NMR. Issue 18 (1st September 2018) - Tanaka, Hiroki; Akutsu, Hideo; Yabuta, Izumi; Hara, Masashi; Sugimoto, Hayuki; Ikegami, Takahisa; Watanabe, Takeshi; Fujiwara, Toshimichi
Abstract : Chitin‐binding domain of chitinase A1 (ChBDC hiA1 ) is characteristic because it binds only to insoluble crystalline chitin. While binding sites of major carbohydrate‐binding modules carry multiple aromatic rings aligned on a surface, lethal mutations for ChBDC hiA1 were reported only at W687, a location completely different from the site mentioned above, in spite of their similar main‐chain folds. Here, the structural mechanism underlying its crystalline chitin binding was uncovered by solid‐state NMR. Based on 13 C‐ and 15 N‐signal assignment of microcrystalline ChBDC hiA1, the chemical shift perturbation on chitin binding was carefully examined. The perturbation was greatest at W687 and nonaromatic residues surrounding it, revealing their direct involvement in chitin binding. These residues and Q679 should provide a novel chitin‐binding platform parallel to the W687 ring. Abstract :